Kinetics of solid state bioconversion for the production of Citric Acid from oil palm empty fruit bunches (abstract only) - Bari, M.N.; Alam, Md. Zahangir; Muyibi, Suleyman Aremu; Jamal, Parveen; Al-Mamun, Abdullah (2009)
A kinetic study of solid state bioconversion for the production of citric acid from oil palm empty fruit bunches was conducted. Locally isolated Aspergillus niger IBO-103MNB (IMI396649) was used for this study. As citric acid production typically exhibits product-associated kinetics, both fungal growth in term of protein content and citric acid production were described with logistic functions and were related to sucrose utilization as carbon source. The estimated specific growth rate was obtained 0.86 d-1 and the citric acid production rate (productivity) was 59.7 g/kg-day. The value of citric acid production yield on sucrose (Yp/s) was 0.77, whereas citric acid production yield on biomass (Yp/x) during the solid state bioconversion of empty fruit bunches was 12.3 g/g of protein content.